The Force of Law of The Agreement on The Transfer of The Right To Charge Receivables (Cessie) Against The Right of Dependents - Marcha Amalia; Mohamad Fajri Mekka Putra (IHSA Institute, 2022)
Based on Law no. 4 of 1996 concerning Mortgage on Land and Objects Related to Land stipulates that mortgage rights must be reinforced by the means of an authentic deed in the form of a Mortgage Granting Deed made before Land Deed Officer (PPAT), and registered at the Land Office with a valid Mortgage Certificate issued. This study aims to examine the transfer of the receivable (cessie) in the case of mortgages that are not registered at the Land Office and are not recorded in a land title certificate, as well as legal protection of third parties as buyers in good faith who occupy the subject of mortgage in the process of transfer of the receivable (cessie). This legal analysis uses a normative juridical method in approaching the relevant provisions of the law. The data collection method used is literature study with qualitative data analysis. The results indicate that the transfer of the receivable (cessie) cannot immediately proceed to the stage of ownership rights transfer and buyers in good faith who have complied with the provisions of SEMA No. 4 of 2016 must first seek additional legal protection of their rights.